Acoustic prediction of helicopter unsteady manoeuvres - Gennaretti, M.; Bernardini, G.; Serafini, J.; Trainelli, L.; Rolando, A.; Scandroglio, A.; Riviello, L.; Paolone, E. (My University, 2015)
Real-time estimation techniques of helicopter noise in manoeuvring flight are examined. They consist of quasi-steady aeroacoustic predictions based on noise-sources (given in terms of hemispheric acoustic maps rigidly connected to the rotorcraft) suitably extracted from a database generated through off-line aeroacoustic analysis of rectilinear, steady-state flights. This is of interest for the Clean Sky GRC5 MANOEUVRES project, which aims at developing an in-flight noise monitoring system to make the pilot aware of acoustic disturbance produced. Considering a helicopter in an approach manoeuvre, the accuracy of the quasi-steady acoustic approaches is assessed by comparison with fully unsteady simulations, and the sensitivity of their predictions on the quality of the estimation of the flight parameters considered to extract the suitable instantaneous hemispheric acoustic maps from the database is examined.
Keywords: Green Rotorcraft